2015
DOI: 10.1194/jlr.m057661
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of autotaxin expression and secretion by lysophosphatidate and sphingosine 1-phosphate

Abstract: This article is available online at http://www.jlr.org Autotaxin (ATX) is a secreted enzyme, which converts extracellular lysophosphatidylcholine (LPC) into lysophosphatidate (LPA). This is an important reaction in cell signaling because LPA activates at least six G proteincoupled receptors to increase cell division, survival, and migration ( 1, 2 ). ATX serves an essential function in embryonic development because ATX knockout mice die in utero at day 9.5 with defects in vasculogenesis and the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 56 publications
(76 reference statements)
10
105
0
Order By: Relevance
“…How the initial secretion relates to the subsequent protein synthesis is not known, but our data suggest not yet described control mechanisms for ATX expression; previous work indicate an inhibitory feedback loop between LPA and ATX in e.g. thyroid and melanoma cell lines [4] . Further work showed that P2X4 and P2X7 co-localize in response to TDI, and that ATX is rapidly concentrated in plasma membrane vesicles, presumably as a step preceding the secretion of ATX.…”
Section: Proof Of Principal: Tdi Is a Potent Activator Of A "P2x-atx"mentioning
confidence: 79%
See 4 more Smart Citations
“…How the initial secretion relates to the subsequent protein synthesis is not known, but our data suggest not yet described control mechanisms for ATX expression; previous work indicate an inhibitory feedback loop between LPA and ATX in e.g. thyroid and melanoma cell lines [4] . Further work showed that P2X4 and P2X7 co-localize in response to TDI, and that ATX is rapidly concentrated in plasma membrane vesicles, presumably as a step preceding the secretion of ATX.…”
Section: Proof Of Principal: Tdi Is a Potent Activator Of A "P2x-atx"mentioning
confidence: 79%
“…Thus, death resulting from hyperoxic toxicity in mice depends on ATX induction in invariant natural killer cells (iNKT cells), often described as a bridge between innate and adaptive immunity, but also depends on extracellular ATP (that is a ligand for P2X7) [31] . Interestingly, not only hyperoxic injury but also hypoxia induce ATX levels [19] , so cell damage might be the common denominator in these studies [19,31] and, as mentioned above, ATX is implicated in wound healing [4] .…”
Section: Diisocyanates Purineric Receptors Sensitization and Innatementioning
confidence: 99%
See 3 more Smart Citations